Comparative analysis of cryopreserved adipose stem cells expanded in hollow fiber bioreactor versus conventional tissue culture flasks - Guoqiang Ren; Morten Brøndum Sørensen; Simone Riis Porsborg; Trine Fink; Vladimir Zachar; Qiuyue Peng (Scientific Reports)
Abstract Cryopreservation enhances the availability of “off-the-shelf” cell therapies. However, the choice between tissue culture polystyrene (TCP) and hollow fiber system (HFB) system for adipose-derived stem cell (ASC) production remains a critical decision, with implications for scalability, reproducibility, and the clinical efficacy. Therefore, the characteristics of ASCs expanded in TCP and HFB and cryopreserved were compared. TCP and HFB cultures were established, and cells were cryopreserved. Surface markers were analyzed to identify immunophenotypic changes and subpopulations. Clonogenicity, differentiation capability, and proliferation potentials were determined along with surrogate tests on wound healing. The expressions of the most markers were consistent before and after thawing for both systems. However, CD105 expression of TCP cells was significantly decreased by the freeze-thawing procedure. Also, CD274 was significantly less expressed on HFB-expanded cells before freezing, however, post-thawing, the proportion of CD274 positive cells was comparable to TCP cells. Besides, two expansions supported different subpopulations, influencing the heterogeneity within ASC cultures. Despite this heterogeneity, no statistical differences were observed as for ASC functional characteristics and the effects on fibroblasts. This study highlighted freeze-thaw does not interfere with the production of fully functional ASCs in either system, although it drives some differential changes in the subpopulations between systems.